Effects of Sargaquinoic Acid in Sargassum Serratifolium on Inducing Brown Adipocyte-like Phenotype in Mouse Adipocytes In Vitro - Kwon, Misung; Lee, Bonggi; Lim, Sujin; Kim, Hyeung-Rak (Planta Medica, 2020)
A previous study showed that the meroterpenoid-rich fraction of an ethanolic extract of Sargassum serratifolium (MES) stimulated adipose tissue browning and inhibited diet-induced obesity and metabolic syndrome. Sargaquinoic acid (SQA) is a major component in MES. We investigated the effects of SQA on the differentiation of preadipocytes to the beige adipocytes. SQA was treated in 3T3-L1 adipocytes differentiated under a special condition that has been reported to induce the browning of adipocytes. SQA at 10 µM reduced lipid accumulation by approximately 23%. SQA at 2.5 – 10 µM induced the differentiation of white adipocytes to beige adipocytes partially by increasing the mitochondrial density and the expression of beige/brown adipocyte markers. In addition, SQA activated lipid catabolic pathways, evidenced by the increased expression levels of perilipin, carnitine palmitoyltransferase 1, and acyl-CoA synthetase long-chain family member 1. As a partial mechanism, biochemical and in silico analyses indicate that SQA activated AMP-activated protein kinase signaling in adipocytes.
Keywords: Sargassaceae; Sargassum serratifolium; lipolysis; sargaquinoic acid; adipocytes